Rabies: an update for nurses in general practice. (2nd December 2019) - Simons, Hilary; Fletcher, Rachael; Russell, Katherine
Abstract : Practice nurses have an important role to play in raising the profile of rabies as a travel-related hazard. Hilary Simons, Rachael Fletcher and Katherine Russell give an update for nurses working in this area of practice Many thousands of human deaths are attributed to rabies infection globally each year; once the symptoms of rabies occur, death is almost always inevitable. Rabies is a zoonosis—a disease of animals that can be transmitted to humans—and can occur in all warm-blooded animals. Rabies remains a neglected disease that impacts most on impoverished and disadvantaged populations living in rabies endemic regions, who may have limited or no access to good healthcare facilities and safe rabies vaccine products. Practice nurses are well placed to raise travellers' awareness of the risk of rabies at a destination, and provide guidance on pre-travel vaccination and post-exposure treatment.